Is Isolated Low High-Density Lipoprotein Cholesterol a Cardiovascular Disease Risk Factor?: New Insights From the Framingham Offspring Study. (May 2016) - Bartlett, Jacquelaine; Predazzi, Irene M.; Williams, Scott M.; Bush, William S.; Kim, Yeunjung; Havas, Stephen; Toth, Peter P.; Fazio, Sergio; Miller, Michael
Abstract : Background—: Although the inverse association between high-density lipoprotein cholesterol (HDL-C) and risk of cardiovascular disease (CVD) has been long established, it remains unclear whether low HDL-C remains a CVD risk factor when levels of low-density lipoprotein cholesterol (LDL-C) and triglycerides (TG) are not elevated. This is a timely issue because recent studies have questioned whether HDL-C is truly an independent predictor of CVD. Methods and Results—: 3590 men and women from the Framingham Heart Study offspring cohort without known CVD were followed between 1987 and 2011. Low HDL-C (<40 mg/dL in men and <50 mg/dL in women) was defined as isolated if TG and LDL-C were both low (<100 mg/dL). We also examined higher thresholds for TG (150 mg/dL) and LDL-C (130 mg/dL) and compared low versus high HDL-C phenotypes using logistic regression analysis to assess association with CVD. Compared with isolated low HDL-C, CVD risks were higher when low HDL-C was accompanied by LDL-C ≥100 mg/dL and TG <100 mg/dL (odds ratio 1.3 [1.0, 1.6]), TG ≥100 mg/dL and LDL-C <100 mg/dL (odds ratio 1.3 [1.1, 1.5]), or TG and LDL-C ≥100 mg/dL (odds ratio 1.6, [1.2, 2.2]), after adjustment for covariates. When low HDL-C was analyzed with higher thresholds for TG (≥150 mg/dL) and LDL-C (≥130 mg/dL), results were essentially the same. In contrast, compared with isolated low HDL-C, high HDL-C was associated with 20% to 40% lower CVD risk except when TG and LDL-C were elevated. Conclusions—: CVD risk as a function of HDL-C phenotypes is modulated by other components of the lipid panel. Abstract : Supplemental Digital Content is available in the text.